Pathophysiologic significance of procoagulant microvesicles in cancer disease and progression - Castellana, D.; Kunzelmann, C.; Freyssinet, J.-M. (Hämostaseologie, 2009)
Microvesicles (MV) are submicrometric membrane fragments (0.1 to 1 μm), released from the plasma membrane of activated or apoptotic cells. They are characterized by most of the antigenic profile of the cells they originate from, and by the presence of procoagulant phospholipids at their surface. MV are detectable in the peripheral blood of mammals and considered as efficient effectors in the haemostatic or thrombotic responses, able to remotely initiate or amplify beneficial or deleterious processes, depending on the circumstances. Variations in their level and pheno-type make them relevant pathogenic markers of thrombotic disorders and vascular damage. To date, MV are recognized as mediators of communication allowing cells to influence a target present in the local microenvironment as well as to at distant sites. The mechanisms by which MV interact with target cells are still unclear, but a number of studies suggest involvement of MV-cell fusion or ligand-receptor interactions. More importantly, MV have been shown implicated in horizontal transfer of genetic material. This review focuses on the role of MV in the context of cancer, and their possible part in cancer associated thrombosis.
Keywords: Microvesicles; tumour microenvironment; thrombosis